Technical note: MR-compatible pedal ergometer with electromechanical pedal resistance and exercise triggering enhanced by visual feedback via video display - Sedivy, Petr; Dezortova, Monika; Rydlo, Jan; Moravec, Petr; Krizek, Ivan; Setinova, Bara; Pajuelo, Dita; Burian, Martin; Hajek, Milan (Medical physics, 2023)
BACKGROUND: During and after exercise, dynamic 31 P MR parameters are typically measured using an MR-compatible ergometer. Self-built equipment for local condition can be constructed where possible. PURPOSE: To develop a pedal resistance ergometer with rocker arm based on a system that combines electric weight displacement, visual self-monitoring, and exercise triggering. The repeatability and reproducibility were tested. METHODS: The hardware and software for the ergometer were constructed from commercial components in a home laboratory. Twelve volunteers participated in the testing of the ergometer. RESULTS: A fully automated ergometer system was developed, allowing the pedal resistance to be adjusted during the examination. The system includes a self-monitoring and triggering mechanism that enables both the operator and subject to monitor pedal frequency and force. The operator can modify the pedal resistance as desired during the exercise. This self-monitoring solution is simple and cost-effective, requiring only a commercial potentiometer, an Arduino converter, and a conventional video projector with a personal computer (PC). Additionally, all system components are located outside the magnetic resonance (MR) room, avoiding interference with the MR system. Results of several test of the reproducibility/repeatability of power at three pedal resistance values (15%, 24%, 25% maximal voluntary force) were expressed both as a coefficient of variation ranging from 6% to 3.1% and as an intraclass correlation of coefficient ranging from 0.96 to 0.99. Similar values were also found for other dynamic parameters of 31 P MR spectroscopy. These findings are similar to published data obtained on different types of ergometers. CONCLUSIONS: Based on more than 1 year of usage, the ergometer proved successful in handling stationary and variable loads, and can be easily operated by a single user.
Keywords: cvičení; magnetická rezonanční spektroskopie; magnetická rezonanční tomografie; Feedback, Sensory; reprodukovatelnost výsledků; Magnetic Resonance Spectroscopy; senzorická zpětná vazba; Magnetic Resonance Imaging; Exercise; Humans; lidé; Reproducibility of Results